ANALISIS PROSES REHABILITASI PSIKOLOGIS PASIEN DENGAN GANGGUAN EMOSIONAL: STUDI KASUS DI PUSAT REHABILITASI ODGJ WELAS ASIH - Rita Silviani; Yahdinil Firda Nadirah (STKIP Subang, 2025)
Emotional disorders are psychological conditions that affect an individual’s ability to regulate emotions, engage in social interactions, and adapt to their environment. In the context of increasing mental health cases in Indonesia, psychiatric rehabilitation services play a crucial role in supporting patient recovery. This study aims to analyze the rehabilitation process of a patient with emotional disorders at the ODGJ Welas Asih Rehabilitation Center and to identify the counseling approaches that contribute to the patient’s psychological improvement. This research employed a qualitative case study design, with data collected through in-depth interviews and behavioral observations. The findings show that the patient experienced significant progress in emotional regulation and social functioning. This improvement was supported by the implementation of Cognitive Behavioural Therapy (CBT), which helped the patient identify and modify negative thinking patterns, as well as humanistic counseling, which provided unconditional acceptance and fostered self-understanding and confidence. The results were further analyzed using Maslow’s Hierarchy of Needs and Erikson’s Psychosocial Development Theory. These frameworks reveal that fulfilling basic needs, ensuring safety, strengthening social belonging, and supporting identity development play essential roles in emotional recovery. A supportive rehabilitation environment, consistent guidance, and structured daily activities also contributed to improved emotional stability and social adaptation. Overall, this study highlights the importance of a multidimensional approach in the rehabilitation of emotional disorders, emphasizing that psychological and social interventions are just as vital as medical treatment in facilitating patient recovery.